Adaptibility of tomato genotypes suitable for coastal region of Patuakhali in Bangladesh - Hasan, MN; Hasan, MM; Haque, MZ; Howlader, MHK; Shanta, UK (Progressive Agriculture, 2017)
A field experiment was carried out at the Regional Horticultural Research Station, Lebukhali, Patuakhali, during the winter. The experiment was conducted to find out adaptive tomato genotypes suitable for coastal Patuakhali region considering their growth and yield performance. The genotypes of this experiment showed significant influence independently on different parameters of tomato plant. The maximum plant height (86.80 cm) was found in BARI tomato-3. The maximum primary (2.55), secondary (9.55) and tertiary branch (4.48) were obtained from BARI tomato-14. The maximum number of leaves (34.93) obtained from BARI tomato-14. The highest length of largest leaves (35.87 mm) was recorded in BARI tomato-3. The maximum number of flower clusters plant-1 (19.47), number of flowers cluster-1 (6.62), number of fruit cluster-1 (4.84), number of flowers plant-1 (126.3), number of fruits plant-1 (88.0), minimum date for 50% flowering(53.33), highest percentage of fruit setting (76.27), minimum days to first harvest (101.7) were obtained from BARI tomato-14. Moreover, BARI tomato-14 also performed better in respect of yield (3.51 kg/plant and 124.8 t/ha). It may therefore concluded that the genotype BARI tomato-14 showed better growth and yield performance under the coastal condition and suitable for Patuakhali region. Progressive Agriculture 28 (2): 84-91, 2017